Who Does What? Tensions between Deans and Department Heads in Defining Roles - Tammy M Proctor; Miguel Martinez-Saenz (Academic Chairpersons Conference Proceedings, 2016)
The session is designed around three common points of tension between deans and department heads created by the blurring of their roles: 1) fundraising; 2) creating a “vision”; 3) budgetary oversight. Attendees will work in groups to develop tools for negotiating each scenario, regardless of institution size or structure.
Keywords: market forces; vision; relationship with Dean; fundraising